2016
DOI: 10.1007/s10600-016-1614-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Diterpene Alkaloids by the Urea–H2O2 Complex

Abstract: Oxidation of the diterpene alkaloids lappaconitine, triacetyllappaconine, and talatisamine by the urea-H 2 O 2 complex (UHP) under various conditions produced the corresponding nitrones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Twenty-four known compounds, nagadine nitrone (2), 3 nagadine (3), 4 piepunensine A (4), 5 liljestrandinine (5), 6 hemsleyaconitine G (6), 7 talatisamine (7), 5 14-acetyltalatisamine (8), 8 14-acetyl-8-methyltalatisamine (9), 9 acoforine (10), 9 14-benzoylaconine (11), 10 indaconitine (12), 8 3-deoxyaconitine (13), 10 columbidine (14), 9 hemsleyanine C (15), 11 cammaconine (16), 12 mesaconitine (17), 10 14-benozylmesaconine (18), 10 hypaconitine (19), 10 N-deethyltalatisamine (20), 6 sachaconitine (21), 13 aconosine (22), 5 akiran (23), 14 dolaconine (24) 15 and vilmorine D (25) 16 were identified by various spectroscopic methods (HR-ESI-MS, IR, NMR) and comparison with literature. Compound 2, a C19-diterpenoid alkaloid with a nitrone functionality, was isolated from natural for the first time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four known compounds, nagadine nitrone (2), 3 nagadine (3), 4 piepunensine A (4), 5 liljestrandinine (5), 6 hemsleyaconitine G (6), 7 talatisamine (7), 5 14-acetyltalatisamine (8), 8 14-acetyl-8-methyltalatisamine (9), 9 acoforine (10), 9 14-benzoylaconine (11), 10 indaconitine (12), 8 3-deoxyaconitine (13), 10 columbidine (14), 9 hemsleyanine C (15), 11 cammaconine (16), 12 mesaconitine (17), 10 14-benozylmesaconine (18), 10 hypaconitine (19), 10 N-deethyltalatisamine (20), 6 sachaconitine (21), 13 aconosine (22), 5 akiran (23), 14 dolaconine (24) 15 and vilmorine D (25) 16 were identified by various spectroscopic methods (HR-ESI-MS, IR, NMR) and comparison with literature. Compound 2, a C19-diterpenoid alkaloid with a nitrone functionality, was isolated from natural for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…430.2593). The IR (KBr) spectrum exibited absorption bands for hydroxyl group (3423 cm −1 ) and 22 R 1 =H, R 2 =H, R 3 =H 23 R 1 =OAc, R 2 =OMe, R 3 =OMe 24 R 1 =H, R 2 =H, R 3 Comparison of the NMR data of 1 with those of sinchianine 18 revealed that they were both C20-diterpenoids with a denudatine skeleton, except for the presence of a carbonyl group at C-15 and the ester side chain at C-13 in compound 1. The planar structure of 1 was further verified by analysis of the HMBC and 1 H-1 H COSY spectra (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation